Implementation of E-Court and Its Impact on Justice Seekers in the Legal Process at the Religious Court - Adella Rofi’ah; Nawa Angkasa (Istinbath : Jurnal Hukum, 2024)
This research aims to find out how the implementation of e-Court according to the Supreme Court Regulations which provides a new breakthrough in the procedural process through electronic mechanisms at the Class IAMetro Religious Courts in particular and its impact on justice seekers in the procedural process. Bearing in mind that justice seekers tend to experience difficulties in carrying out activities in court during the proceedings, where justice seekers must come to the court first. This will take time and money to implement, of course it will also make services less efficient and effective in case registration and trial processes. The most important essence is in resolving cases electronically where the Religious Courts are one of the authorities that handles cases at the first level. This is the embodiment and realization of the hope of the existence of this system for the justice seeking community which can provide benefits which are made easier so that the process of proceedings can be carried out smoothly. effective and efficient. The method used in this research is qualitative and is described using primary data sources and secondary data sources. Primary data sources are from Legal Aid Posts, Case Managers/PTSP, Secretaries, Registrars, Judges and Justice Seekers at Class I A Metro Religious Courts who are informants. Apart from collecting interview results and documentation, this research was also carried out by carrying out structured data processing using inductive thinking methods.